Association of Megsin Gene Variants With IgA Nephropathy in Northwest Chinese Population: A STROBE-Compliant Observational Study. Issue 6 (February 2016) - Wei, Lin-Ting; Fu, Rong-Guo; Gao, Jie; Yu, Qiao-Ling; Dong, Feng-Ming; Wang, Zhe; Wang, Meng; Liu, Xing-Han; Dai, Zhi-Jun
Abstract : Abstract: Megsin is a mesangial cell-predominant gene that encodes a serpin family protein which is expressed in the renal mesangium. Overexpression of megsin has been observed in the glomeruli of patients with IgA nephropathy (IgAN). The aim of this study was to evaluate the association of megsin polymorphisms (rs1055901 and rs1055902) with IgAN in a Chinese population. We examined 351 patients with histologically proven IgAN and compared them with 310 age, sex, and ethnicity-matched healthy subjects. Two single nucleotide polymorphisms (SNPs) in megsin were genotyped by Sequenom MassARRAY. SPSS 18.0 was used for statistical analyses, and SNP Stats to test for associations between these polymorphisms and IgAN risk. Odds ratios with 95% confidence intervals were used to assess the relationships. We found that rs1055901 and rs1055902 SNPs were not correlated with susceptibility to IgAN in Northwest Chinese population. Analyses of the relationship between genotypes and clinical variables indicated that in patients with IgAN, rs1055901 was associated with 24-hour proteinuria, an increase in blood pressure, and Lee's grade ( P  = 0.04, 0.02, and 0.04, respectively), and rs1055902 was associated with 24-hour proteinuria and Lee's grade ( P  = 0.03 and 0.01, respectively). However, the results showed no association between these gene variants and sex of the patients. These results indicate that megsin gene variants may play a role in the severity, development, and/or progression of IgAN in Northwest Chinese population.